Newspapers` Reportage and Perception of Yenagoa Residents of Climate Change and Adaptation in Bayelsa State, Nigeria - Jammy Seigha Guanah (Utan Kayu Publishing, 2024)
Climate change has been identified as a significant threat to human and natural systems, with many communities around the world being adversely affected. The impact of climate change is especially pronounced in the Niger Delta region of Nigeria, Bayelsa State, where rising sea levels, increased flooding, and erosion threaten the lives and livelihoods of the population. This study explored media reportage on climate change and adaptation in Bayelsa State, Nigeria, with a focus on Yenagoa, the State`s capital. Using a quantitative approach, the study analysed newspapers` (Vanguard, The Sun, and Punch newspapers) reportage of climate change issues from October 2022 to March 2023; assessed the level of public awareness of climate change and its impacts; and examined the effect of climate change on Yenagoa and the perception of its residents on their attitudes towards climate change adaptation. The Agenda Setting Theory was used for this study. Data were collected through the use of a self-administered questionnaire distributed to a representative sample of the adult population in Yenagoa. Also, Content Analysis method was adopyed. The findings indicated that newspapers` reportage on climate change in Bayelsa State is limited and that the public has a low level of awareness on the subject. The study recommended the need for increased media attention to climate change issues, and the importance of public education and awareness-raising efforts to promote climate change adaptation in the region.